Pengaturan Tenaga Kerja Asing di Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 169/PUU-XXI/2023 - Arifin, Ahmad; Fenny Fatriani (LP3M IAI Al-Qolam, 2024)
This study examines the regulation of foreign workers (TKA) in Indonesia and the implications of the Constitutional Court Decision Number 168/PUU-XXI/2023 on TKA regulations. The focus is to analyze regulatory changes before and after the decision, as well as its impact on prioritizing local workers, technology transfer, and TKA licensing. This research employs a normative juridical method with a statutory approach, based on an analysis of legal documents such as laws and court decisions. The findings reveal that the Constitutional Court's decision strengthens the prioritization of local workers, technology transfer, and TKA oversight. The implementation of this decision is expected to reduce reliance on foreign workers, enhance the competitiveness of local labor, and promote inclusive development. The government is urged to reinforce oversight, prioritize training for local workers, and conduct periodic evaluations of TKA policies to support the independence of Indonesian labor in the global era